General Concept Of Sensation. Types Of Sensation And Its Laws - Ne'matova.D.Sh; Oymatova Dilorom Ro'zimurotovna (Euro Asian Journal Publishing, 2025)
Sensation is a process that plays an important role in human life. In every person’s cognitive process, sensations have a significant function. This article analyzes the scientific and psychological basis of the concept of sensation, its role and importance in human cognition. It provides detailed information about the main types of sensation – vision, hearing, smell, taste, and touch. Each type of sensation is studied separately, explaining how they are perceived through sensory organs, the role of analyzers, and the laws involved in the sensation process. In addition, the article focuses on the differences between sensation and perception, as well as psychological phenomena such as sensitivity, adaptation, and sensory thresholds.
Keywords: Sensation; analyzer; vision; hearing